Ethology, mandibular dimorphism in the larvae, and spinning of the cocoon in the subfam. Heterarthrinae (Hymenoptera Tenthredinidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
The A. has bred in Northern Italy 6 of the 7 European species of the subfam. Heterarthrinae: Heterarthrus microcephalus (Klug) from willow, H. vagans (Fallén) from alder, H. nemoratus (Fallén) from birch, all have 2 generations per year; H. ochropodus (Klug) from poplar, H. aceris (MacLachlan) and H. leucomelus (Klug) from maple, have 1 generation per year.General information is given on the systematic position of the genus Heterarthrus. For each species the life cycle has been ascertained as well as the ethology of the larvae, namely their feeding habits and the formation of the cocoon. A review is made of the host trees.The larvae have 6 or 7 instars; in their first 5 or 6 instars they all have subpyramidal mandibles, depressed dorso-ventrally; the larvae of the last instar are aphagous and have sharp pointed punch-like mandibles, that are to be considered as atrophic regressing organs having lost their masticatory functions; they are used by the larva to support the spinnaret, when spinning the cocoon, though they never touch the silk threads.The lens-shaped cocoon is spun inside the blotch mine, a little before or a little after the mined leaves fall down from the tree. The only exception is record ed in H. aceris: the leaf mined by this species does not fall down. The larva of the penultimate instar cuts in the superior epidermis of the mined leaf 20-30 very small slits, separating a round area (4,5-6,5 mm in diameter) that remains attached to the mine because of small parts of dry epidermis between the slits. Immediately after the larva moults and spins its cocoon attached to the said circular area of epidermis. Soon after, as a consequence fo the shrinking of the drying walls of the mine and of the harsh movements of the larva inside the cocoon this one detaches from the leaf and falls down to the ground. Because of the stirring of the larva inside the cocoon this one moves on the ground disappearing under the litter and in the soil crevices.The males of H. nemoratus are unknown, those of H. aceris very rare; for this reason thelitokous parthenogenesis is admitted for these species. For H. vagans and H. ochropodus whose males are aboundant the arrhenotokous parthenogenesis has been demonstrated.
Keywords: Tenthredinoidea Heterarthrinae; mandibular dimorphism in the larvae; cocoon spinning